STRATEGI PEMASARAN PESAN KELANGKAAN PADA PENJUALAN PRODUK FASHION THRIFT DALAM MEMENGARUHI PERILAKU PEMBELIAN IMPULSIF PADA KONSUMEN - Bahar, Andrieta Chika; Nugeraha, Prasetya (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2024)
Thrift fashion is one of the current fashion trends that are busy among fashion consumers. A good marketing strategy used in marketing this thrift fashion is the scarcity message marketing strategy. This study aims to determine how much influence scarcity messages have on impulse buying behaviour among consumers in Bandar Lampung. The type of research used is quantitative research using the explanatory research method. The population in this study were consumers of thrift fashion products in Bandar Lampung with a sample size of 96 respondents who were taken using purposive sampling technique. The data sources used are primary data and secondary data. Data were collected through questionnaires. The data in this study were analysed using simple regression analysis. The results of this study indicate that the scarcity message variable has a significant effect on impulse buying behaviour with an R square value of 0.515 or 51.5%.